Characterization of Free and Porous Silicon-Encapsulated Superparamagnetic Iron Oxide Nanoparticles as Platforms for the Development of Theranostic Vaccines - Lundquist, Charles M. (2014)
Tracking vaccine components from the site of injection to their destination in lymphatic tissue, and simultaneously monitoring immune effects, sheds light on the influence of vaccine components on particle and immune cell trafficking and therapeutic efficacy. In this study, we create a hybrid particle vaccine platform comprised of porous silicon (pSi) and superparamagnetic iron oxide nanoparticles (SPIONs). The impact of nanoparticle size and mode of presentation on magnetic resonance contrast enhancement are examined. SPION-enhanced relaxivity increased as the core diameter of the nanoparticle increased, while encapsulation of SPIONs within a pSi matrix had only minor effects on T2 and no significant effect on T2* relaxation. Following intravenous injection of single and hybrid particles, there was an increase in negative contrast in the spleen, with changes in contrast being slightly greater for free compared to silicon encapsulated SPIONs. Incubation of bone marrow-derived dendritic cells (BMDC) with pSi microparticles loaded with SPIONs, SIINFEKL peptide, and lipopolysaccharide stimulated immune cell interactions and interferon gamma production in OT-1 TCR transgenic CD8(+) T cells. Overall, the hybrid particle platform enabled presentation of a complex payload that was traceable, stimulated functional T cell and BMDC interactions, and resolved in cellular activation of T cells in response to a specific antigen.